Elderly Profile of Quality of Life Using WHOQOL-BREF Indonesian Version: A Community-Dwelling - Hidayati, Aghnia Rizki; Gondodiputro, Sharon; Rahmiati, Lina (Althea Medical Journal, 2018)
Background: Indonesia as one of the developing countries is facing a demographic transition. The proportion of under-five children is decreasing while the proportion of elderly is rising. This situation is followed by the increase of noncommunicable/degenerative diseases. However, this situation is not a constraint for the elderly to have a better life. The WHOQOL Group had developed a questionnaire to measure the elderlyâs quality of life. The aim of this study was to describe the quality of life (QoL) of a community-dwelling elderly by using the WHOQOL-BREF questionnaire Indonesian version.Methods: Eighty eight elderly from 6 villages in Jatinangor, West Java, Indonesia were involved in a descriptive study relating to QoL by using the WHOQOL-BREF questionnaire Indonesian version.Â The inclusion criteria were men and women, aged â¥60 years, could communicate effectively, and had Mini Mental State Examination score â¥>23. The variables in the study were physical, psychological, social and environmental domains and facets in the QoL questionnaire. The collected data in the study were analyzed using the central tendency items.Results: Most respondents had low QoL scores (â¤60). This study discovered that some facets of every domain in the WHOQOL-BREF had low scores, namely adequate energy, ability to perform daily living activities, satisfaction with work capacity, ability to concentrate, acceptance of physical appearance, satisfaction of sex life, financial fulfillment, availibility of information, opportunity for leisure activities and transport.Conclusions: Most of the elderly have low QoL scores in some facets of every domain in the WHOQOL-BREF questionnaire.Â Â